Countercyclical capital buffers and credit supply: Evidence from the COVID-19 crisis - Dursun-de Neef, H． Özlem; Schandlbauer, Alexander; Wittig, Colin (Journal of Banking & Finance, 2023)
This paper examines how European banks adjusted their lending subsequent to the release of the countercyclical capital buffers (CCyB) during the COVID-19 pandemic. At its onset in 2020Q1, being exposed to a higher ex-ante countercyclical capital buffer led to a reduction in banks' lending. Yet the relief of the CCyBs removed this negative effect from 2020Q2 onwards. We find that the reduction in CCyBs led to a significant relative increase in the average bank's lending by about 5.6 percentage points of their total assets. This increase happened mainly in retail mortgage loans and was stronger for poorly-capitalized banks. These results imply that the release of the CCyBs was effective in promoting bank lending during the pandemic.